(untitled) (CIPEEX, 2025)
Knowing that there are important obstacles to the penetration of rural insurance among family agricultural producers, it is important to note the repercussions resulting from the insured not receiving compensation due to confusing clauses provided for in insurance policies, more precisely in their special and general conditions. It is patent to discuss, therefore, the relationships arising from the securitization of rural economic activities, or rather, agribusiness, and the demand for the protections of the Consumer Protection Code. The guiding hypothesis of the work considers a certain worsening of the vulnerability of small rural producers in a consumer relationship involving banks and insurance companies. Hence the reason for the study to point out the impact of consumer protections in promoting the economic activity carried out by small rural producers, notably when such activity is, or at least should be, protected by taking out a type of insurance. Knowing that there are important obstacles to the penetration of rural insurance among family agricultural producers, it is important to note the repercussions resulting from the insured not receiving compensation due to confusing clauses provided for in insurance policies, more precisely in their special and general conditions. It is patent to discuss, therefore, the relationships arising from the securitization of rural economic activities, or rather, agribusiness, and the demand for the protections of the Consumer Protection Code. The guiding hypothesis of the work considers a certain worsening of the vulnerability of small rural producers in a consumer relationship involving banks and insurance companies. Hence the reason for the study to point out the impact of consumer protections in promoting the economic activity carried out by small rural producers, notably when such activity is, or at least should be, protected by taking out a type of insurance.